Effect of time and storage temperature on hematological parameters of healthy dogs - Libano de Souza, Kamila (Pubvet, 2020)
The aim of this study was to evaluate the stability of hematological parameters at different storage times and temperatures. Whole blood from 7 healthy dogs (Canis lupus familiaris) was used. The samples were divided into 2 aliquots of 2 mL stored in EDTA-K3 tubes, kept at room temperature at 22º C and refrigerated at 4º C, in the following time intervals T0h, T6h, T12h, T24h, T48h. The exams were performed in SDH-3 VET® hematology analyzer. The hematological variables were stable over time with the exception of red blood cells that underwent variation at T12h at room temperature and platelets that at T6h at room temperature and under refrigeration remained below the reference range. It is concluded that the samples of dogs analyzed by the impedance technology, more specifically by the labtest SDH-3 VET® equipment, were stable for 48 hours for red blood cell count, hemoglobin concentration, hematocrit and total leukocytes; however, the platelets should be performed with samples taken within 6 hours.
Keywords: stability; haematological; platelets